Analisis Perubahan Suhu Permukaan Laut di Wilayah Laut Flores dan Sekitarnya Menggunakan Citra Aqua Modis - Paramartha, I Gusti Putu Wahyu; Nurweda Putra, I Dewa Nyoman; Astawa Karang, I Wayan Gede (Journal of Marine Research and Technology; Vol 7 No 2 (2024): OKTOBER 2024DO - 10.24843/JMRT.2024.v07.i02.p14, 2024)
Aqua MODIS satellite is one of the satellite methods that can measure sea surface temperature (SST) spatially and temporally. The purpose of this study is to determine changes in sea surface temperature and determine the correlation of SPL with the El Nino Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) phenomena for 20 years from 2003 to 2022 in the Flores Sea Waters and surrounding areas. The data processing consists of pre-processing, processing, and spatial and temporal analysis. The processing results will be presented temporally and spatially to observe monthly, seasonal, and annual fluctuations. The analysis used to determine the relationship between sea surface temperature with ENSO and IOD uses the Pearson correlation equation. The highest monthly average SST occurred in December at 30.63°C, while the lowest occurred in August at 27.67°C. The lowest monthly average SPL in 20 years occurred during August 2006 at 26.86°C. For seasonal SPL, the highest occurred in the west season with an average of 30°C, then the lowest occurred in the east season with an average of 28.15°C. For the annual average value of SPL, the lowest occurred in 2006 at 28.81°C, and the highest occurred in 2016 with an average value of 30.15°C. The correlation value of the relationship between SPL with ENSO and IOD correlates from very low to strong .